Echocardiographic Patterns in Severe Chronic Kidney Disease with Type 4 Cardiorenal Syndrome Patients (TAJ: Journal of Teachers Association, 2022)
Changes in cardiac structure and function detected by echocardiography are common in patients with type 4 cardiorenal syndrome and have been recognized as key outcome predictors. This study aimed to evaluate echocardiographic patterns in severe chronic kidney disease CKD in type 4 cardiorenal syndrome patients. This was a descriptive type of cross-sectional study. The study was carried out in the Cardiology and Nephrology Department of Bangabandhu Sheikh Mujib Medical University, Dhaka. After exclusion total of 44 patients having severe CKD (GFR